1996
DOI: 10.1016/s0969-2126(96)00063-9
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of the light-harvesting complex II (B800–850) from Rhodospirillum molischianum

Abstract: The light-harvesting complexes from different bacteria assume various ring sizes. In LH-2 of Rs. molischianum, the Qy transition dipole moments of neighbouring B850 and B800 BChl-as are nearly parallel to each other, that is, they are optimally aligned for Föster exciton transfer. Dexter energy transfer between these chlorophylls is also possible through interactions mediated by lycopenes and B850 BChl-a phytyl tails; the B800 BChl-a and one of the two B850 BChl-as associated with each heterodimeric unit are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
1,197
3
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,044 publications
(1,229 citation statements)
references
References 69 publications
23
1,197
3
2
Order By: Relevance
“…The primary components of chromatophore vesicles in purple bacteria, as depicted in Figure 1, are, in order of energy utililization (Cogdell et al, 2006,Cartron et al, 2014: (i) light harvesting complex 2 (LH2) (Koepke et al, 1996;Papiz et al, 2003); (ii) light harvesting complex 1 (LH1 Sener et al, 2009]); (iii) RC (Jamieson et al, 2002;Strümpfer and Schulten, 2012a); (iv) cytbc 1 (Crofts, 2004;Crofts et al, 2006); and (v) ATP synthase (Feniouk and Junge, 2009;Hakobyan et al, 2012). RC-LH1 complexes typically form dimeric RC-LH1-PufX complexes facilitated by the polypeptide PufX Sener et al, 2009), although monomeric complexes are also found in membranes from photosynthetically grown cells at a ratio of approximately 10% .…”
Section: Supramolecular Organization Of a Chromatophore Vesicle Adaptmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary components of chromatophore vesicles in purple bacteria, as depicted in Figure 1, are, in order of energy utililization (Cogdell et al, 2006,Cartron et al, 2014: (i) light harvesting complex 2 (LH2) (Koepke et al, 1996;Papiz et al, 2003); (ii) light harvesting complex 1 (LH1 Sener et al, 2009]); (iii) RC (Jamieson et al, 2002;Strümpfer and Schulten, 2012a); (iv) cytbc 1 (Crofts, 2004;Crofts et al, 2006); and (v) ATP synthase (Feniouk and Junge, 2009;Hakobyan et al, 2012). RC-LH1 complexes typically form dimeric RC-LH1-PufX complexes facilitated by the polypeptide PufX Sener et al, 2009), although monomeric complexes are also found in membranes from photosynthetically grown cells at a ratio of approximately 10% .…”
Section: Supramolecular Organization Of a Chromatophore Vesicle Adaptmentioning
confidence: 99%
“…The proteins that constitute the chromatophore are primarily the light harvesting (LH) complexes, photosynthetic reaction centers (RCs), cytbc 1 complexes, and ATP synthases, which cooperate to harvest light energy for photophosphorylation. The architecture of the chromatophore, reported in (Ş ener et al, 2007, 2010Cartron et al, 2014), has been determined by combining atomic force microscopy (AFM) (Bahatyrova et al, 2004;Olsen et al, 2008), cryo-electron microscopy (cryo-EM) (Qian et al, 2005;Cartron et al, 2014), crystallography (Koepke et al, 1996;McDermott et al, 1995;Papiz et al, 2003;Jamieson et al, 2002), optical spectroscopy Sener et al, 2010), mass spectroscopy (Cartron et al, 2014), and proteomics (Jackson et al, 2012;Woronowicz and Niederman, 2010;Woronowicz et al, 2013) data. The composition of the chromatophore depends on growth conditions such as light intensity (Adams and Hunter, 2012;Woronowicz et al, 2011bWoronowicz et al, , 2011a) and can also be influenced by mutations Hsin et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…However, electron microscopy on Rb. sphaeroides LH2 complexes suggests a hexameric structure indicating a (R ) 6 organization. 15 Rsp.…”
Section: Introductionmentioning
confidence: 99%
“…Expectedly, this fraction is zero for all fluences at the repetition rate of 81 kHz as the time delay between two successive pulses of about 12 μs exceeds the lifetime of the triplet state by at least a factor of 5. For the other three repetition rates the fraction of RC-LH1 complexes that carry 3 Car* states on the LH1 ring increases by several orders of magnitude with increasing fluence; see Figure 8A. Representing the same data as a function of the repetition rate for the cw equivalent excitation intensities, Figure 8B, reveals for all intensities an increase of the triplet population for rising the repetition rate from 810 kHz to 8.1 MHz, which levels off for a further increase of the repetition to 81 MHz.…”
Section: ■ Results and Discussionmentioning
confidence: 99%